Familial defect of apolipoprotein В-100: molecular disease basis and clinico-biochemical characteristics of the patients - P. P. Malyshev; A. N. Meshkov; L. A. Kotova; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To identify character and prevalence of apolipoprotein (apo) B-100 gene mutation in patients with clinical diagnosis of heterozygote familial hypercholesterolemia (FH); to describe its phenotypical features in mutation carriers. Material and methods. In 111 patients with clinical diagnosis of heterozygote FH, screening for exon 26 apo B-100 gene mutations was performed. For DNA analysis, allele-specific PCR, restriction analysis, analysis of DNA single-strand conformation polymorphism (SSCP), and sequestering of DNA fragments with anomaly electrophoretic activity were used. Results. In patients with clinics of heterozygote FH, 4,5% had apo B-100 gene mutation. R3500Q mutation was the only apo B-100 gene structure anomaly observed in these individuals. Compared to patients with low-density lipoprotein (LDL) receptor mutation, subjects with apo B-100 defect had less manifested HCH. Conclusion. R3500Q mutation of apo B-100 gene, together with LDL receptor mutations, partially explain high CH levels in Russian patients. Other mutations of this protein’s exon 26 could be very rare.